Harnessing Digital Technologies in Public Pension Reforms (African Journal of Public Administration & Management, 2026)
Public pension funds might not be the first thing that springs to mind when considering the effects of digital technologies. However, just as new technologies are rapidly changing the way the entire financial services sector operates, it is also creating a structural shift in how public pension funds are managed. Given the significant investment portfolio and fund size managed by public pension funds, digital technologies significantly influence national financial markets and investment strategies. Socially, they ensure retirees have a stable income, thereby alleviating pressure on state welfare systems, such as Zambia’s social cash transfer program. The study aimed to explore the influence and intricacies of digital technologies, their implications, and the future trajectories on public pension funds management and reforms within the context of Zambia’s National Pension Scheme Authority (NAPSA). Employing a mixed-methodology approach, the research combined qualitative and quantitative data. Analysis was conducted using Microsoft Excel and SPSS version 31, complemented by an interpret interpretivist perspective on industry fundamentals. Findings revealed that over 95% of its contributors and 60% of its claimants adopted digital platforms over the last five years resulting in enhanced operational efficiency and improved service delivery. Additionally, digital technologies have strengthened NAPSA’s capacity to adapt swiftly to legislative changes and environmental shifts, thereby increasing the agility and effectiveness of pension reforms. The research concludes with recommendations for policymakers and practitioners, emphasizing the need for ongoing investment in digital infrastructure, cybersecurity, and capacity building to sustain the progress made. Strengthening policy frameworks and fostering digital literacy among contributors are essential steps toward realizing the full potential of technology-driven reforms in public pension systems.